Dampak Pandemi Covid-19 terhadap Efektifitas E-Learning Di Labuan Bajo Sebagai Destinasi Pariwisata Super Premium - Berybe, Gregorius Antariksa; Siagiana, Reynaldo Angga; Rambunga, Richard Antonius (Ridwan Institute, 2021)
The purpose of this study is to find out the impact of the Covid-19 pandemic on the effectiveness of e-learning in reducing the spread of the Covid-19 virus in the campus environment while maintaining the quality of the teaching and learning process. The design of the research in this research is a descriptive quantitative method. Data obtained by data collection techniques through questionnaires given to Polytechnic students Elbajo Commodus with analysis of factors such as: a) motivation; b) material or content; c) interaction; d) technology; e) internet access and fees; and f) geography. The results showed that there are several factors that affect the effectiveness of online learning where 79.6% of respondents are not motivated by online learning systems. The lack of interaction between students and lecturers during the online learning process was seen in 38% of respondents who disagreed that the online learning process was effective due to the vagueness of the material voice and virtual learning thus lowering the respondent's understanding. Another factor, where 68.4% of respondents agreed that unstable internet access and high cost made them not get an effective lerning process. The cost itself is related to the livelihoods of parents of students whose 85% are farmers living in the countryside. Online learning during the Covid-19 pandemic affects the effectiveness of the teaching and learning process.